2018
DOI: 10.4269/ajtmh.18-0426
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Flaviviruses Near the Mexico–U.S. Border: Co-circulation of Dengue Virus Serotypes 1, 2, and 3 and West Nile Virus in Tamaulipas, Northern Mexico, 2014–2016

Abstract: A clinical, serological, and molecular investigation was performed to determine the presence of dengue virus (DENV) and other flaviviruses among residents of the city of Reynosa, Tamaulipas, on the Mexico-U.S. border in 2014-2016. The sample population consisted of 2,355 patients with suspected dengue, in addition to 346 asymptomatic individuals recruited during a household-based epidemiological investigation designed to identify flavivirus seroconversions. Sera were collected from patients with suspected deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Diversion of vector bites to non-human competent hosts reduces viral amplification and reduces potentially infectious bites to humans by dengue vectors, thus could be used as a control tool to limit arbovirus transmission. Although an earlier study in a similar Reynosa neighborhood isolated CHIKV from patients with dengue-like symptoms [56], and co-circulation of DENV1-3 and West Nile virus [57], all pools of host-seeking Ae. aegypti were negative for the presence of arbovirus RNA (DENV 1-4, ZIKV, and CHIKV), and all pools of Cx.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 87%
“…Diversion of vector bites to non-human competent hosts reduces viral amplification and reduces potentially infectious bites to humans by dengue vectors, thus could be used as a control tool to limit arbovirus transmission. Although an earlier study in a similar Reynosa neighborhood isolated CHIKV from patients with dengue-like symptoms [56], and co-circulation of DENV1-3 and West Nile virus [57], all pools of host-seeking Ae. aegypti were negative for the presence of arbovirus RNA (DENV 1-4, ZIKV, and CHIKV), and all pools of Cx.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 87%
“…Few records exist of WNV in human samples [19–22], and in three pools of mosquitoes [19, 22]. In the State of Chihuahua, antibodies to West Nile have been isolated in samples of horses, goats, and several species of wild and poultry birds [7], and up to 5.13% in human samples in a cohort study [23] showing local transmission in Ciudad Juárez, Chihuahua.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still no approved antiviral drugs available for the prevention or treatment of DENV and/or ZIKV infection. As several studies have shown that DENV and ZIKV concurrently outbreak in endemic areas [28,29], the development of antiviral agents that act on the host factors are more likely to have pan-antiviral activity, acting not only against DENV but also simultaneously against related flaviviruses, such as ZIKV.…”
Section: Discussionmentioning
confidence: 99%